Globalized weaponry - Gabelnick, Tamar (Social justice, 2000)
Part of a special issue on neoliberalism, militarism, and armed conflict. The writers contend that although the U.S. arms export policy was set in place to protect national security, it has become increasingly focused on commercial interests. They point out that excess arms production capacity and a decrease in demand make sales in the post-cold war global arms marketplace very competitive. They also discuss the globalization process with regard to U.S. weapons sales and production and present some recommendations for a new foreign policy.